THE EFFECT OF VIRTUAL TEACHING ON ATTITUDES OF SECOND LANGUAGE ACQUISITION DURING COVID 19 CONDITIONS OF INDONESIAN STUDENTS - Kandati, Susi P.; Tatipang, Devilito P. (English Education Department, 2021)
The intention of this study is to find out the effect of virtual teaching on attitudes of second language acquisition during Covid 19 condition Most school quickly closed to protect the students and teachers from the virus The study findings indicate that Virtual Teaching VT marked a positive change in the attitudes of the students This study was performed both qualitatively and quantitatively In order to find out the effect of virtual teaching on second language acquisition attitudes a questionnaire was distributed It was conducted at the Senior High School level The questionnaire was distributed among 77 third year students of random Senior High School with a google form sent through WhatsApp due to the outbreak of Covid 19 pandemic It was designed on five linear scales with strongly disagreed 1 disagreed 2 neutrality 3 agreed 4 and strongly agreed 5 options which use English and Bahasa Indonesia Research results show that virtual teaching VET marks a positive change in students attitudes < p>